STRATEGI POLITIK IDRIS AHMAD PADA PEMILU LEGISLATIF 2019 DI DAERAH PEMILIHAN JAKARTA PUSAT - Pelawi, Esra; Apriani, Kadek Dwita; Noak, Piers Andreas (Jurnal Nawala Politika, 2022)
This study aims to understand how Idris Ahmad's political strategy in the 2019 Jakarta legislative election. This research uses a qualitative approach with a case study method. This data was obtained by from 5 informants. Based on the results, it can be concluded that Idris Ahmad's political strategy to get votes and also sympathy from the public in the Central Jakarta electoral area in the 2019 Jakarta legislative election is to use the method explained by the theory of Political Marketing which is divided into 4P, including: Product (Having a good political career in society), Promotion (Conducting campaigns with the community), Price (Having capital in conducting campaigns), Place (The right target in obtaining a lot of votes) and also supported by doing a direct blusukan or dor to dor that prioritizes the interests of the community to get votes and sympathy so that he is elected to the Jakarta DPRD. Keyword: Political Strategy, Jakarta DPRD, Elections